Counselling Muslim couples and families: Practitioners' experiences - Dini Farhana Baharudin; Mohd Zaliridzal Zakaria; Suhailiza Md. Hamdani; Marina Munira Abdul Mutalib; Mahmud, Zuria; Sumari, Melati (Serials Publications, 2024)
Indexed by SCOPUS